Estratégia de manutenção centrada em confiabilidade : estudo de caso de uma prestadora de serviços no setor da construção civil - Freitas, Luis Gabriel Morales Lima de (2022)
Civil construction is one of the most important sectors for a country, as it influences the economy and its development, as in the infrastructure part. In Brazil, the sector participates in a considerable way in the Gross Domestic Product, in addition to generating a wide range of quality jobs, being the most responsible in some states and municipalities for the generation of jobs. Therefore, it is of paramount importance that the equipment of this branch remains in full operating conditions. In this way, maintenance and its tools are necessary, as it addresses several techniques, administrative and supervisory actions, in order to keep the assets always in operating conditions. With this in mind, the present work aims to define a maintenance strategy for the equipment of a service provider in the field of civil construction, in the city of Bagé-RS, using the criticality algorithm tool of the SIGMA software, together with the methodology of Reliability Centered Maintenance. Through this method and tool, it was possible to achieve the specific objectives of the study, in which the equipment can be classified according to its criticality; define the pilot equipment and its adequate maintenance method, in addition to carrying out the application of the FMEA spreadsheet. In this way, the main objective was reached, where preventive maintenance is the most recommended for the company. Finally, a future work is proposed, using maintenance planning and control as a basis, in which it seeks to define strategic actions for maintenance results.